PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA DOSEN DI UNIVERSITAS KRISTEN SURAKARTA - Suprihatmi Sri Wardiningsih, Tri Wibowo Kusumo, Amin Wahyudi & (Universitas Slamet Riyadi, 2017)
This research aims to know the significant effects between: (1)Leadership on performance lecturer, (2) the work environment onperformance Lecturer (3) the motivation on performance lecturer at theChristian University of Surakarta. The population in this research is a lecturerat the Kristen University of Surakarta with the amount of 36 people.Determination of random samples with a total of 30 people. Engineering datacollection using the now through the test validity and reliability. Using linearregression analysis techniques with classic assumption test double. Analysisof the results obtained (1) the now valid, the now leadership variableenvironment variables work valid, the now valid motivation variables.Reliability test result is reliability, (2) Test multicolinearity testheteroscedastisity test passes, passes a test, the test passes, theautocorrelation test normality test and the test passes.Keywords: leadership, work environment, motivation, performance lecturer